Contextual proximities: Framing transnational Filipino masculinities in East Asia - Guevarra, Mary Harmony I. (Animo Repository, 2024)
This cultural studies project on transnational Filipino masculinities in East Asia traverses through an array of cultural narratives that highlight the sensibilities and experiences of male migrant workers in the 21st century, whose lives and labor are informed by the labor export realities of the Philippines, which are largely comprised of the experiences and plights of female migrant workers. This study focuses on three groups of Filipino migrant men employed under specific globalized labor markets of the 21st century that closely operate and/or associate with the physical and discursive spaces of female migrants within an East Asian economy: (1) illegal day laborers or tachinbos in Japan, (2) trafficked migrant fishermen in Taiwan, and (3) male domestic helpers in Hong Kong. This study offers the framework of contextual proximities which posits that the communal sensibilities and specific contexts under female export labor serve as integral components in the examination of migrant masculinities, for these sensibilities and contexts offer discursive pathways that give voice to identity markers, experiences, and sentiments that migrant men might find challenging to recognize and articulate in cultural narratives by and about them. This study examines how the intricate dynamics of their respective labor markets and their operationalization with and/or alongside female migrants within the market inform the cultural politics of their transnational masculinities. I attempt to examine how globalization has brought forth contemporary forms of vulnerabilities and sensibilities to their gender politics, illustrating how Filipino transnational masculinities are evolving in the 21st century.